10(9-x)+x=12(9-x)

Simple and best practice solution for 10(9-x)+x=12(9-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(9-x)+x=12(9-x) equation:



10(9-x)+x=12(9-x)
We move all terms to the left:
10(9-x)+x-(12(9-x))=0
We add all the numbers together, and all the variables
10(-1x+9)+x-(12(-1x+9))=0
We add all the numbers together, and all the variables
x+10(-1x+9)-(12(-1x+9))=0
We multiply parentheses
x-10x-(12(-1x+9))+90=0
We calculate terms in parentheses: -(12(-1x+9)), so:
12(-1x+9)
We multiply parentheses
-12x+108
Back to the equation:
-(-12x+108)
We add all the numbers together, and all the variables
-9x-(-12x+108)+90=0
We get rid of parentheses
-9x+12x-108+90=0
We add all the numbers together, and all the variables
3x-18=0
We move all terms containing x to the left, all other terms to the right
3x=18
x=18/3
x=6

See similar equations:

| -5(-11r+20)=20+14r+11r | | m4−3=7 | | 10n+7=17+10n-10 | | 8÷t=4;t=2 | | 6+6(2t-1)=30+2t | | 15r+8=-16+15r-17 | | 3.4=2.f | | 6r-4=94 | | 3x^2-5x-130=0 | | 6+6(2t-1)=30+2t | | 17+4y=4y-3+20 | | 10(x-3)+x=4(x+x-3)+6 | | -2/3=25y3/4 | | 0=m-11 | | 5/15=3y | | 5=4+z/4 | | 6t+12=3(t-7)+6t | | 3/6=h/12 | | 22=k+20 | | 5.50+75x=3.10+1.35x | | x-5/6=-4 | | 2(x-34)=(-15) | | 4(2b-6)+11=6b+13 | | -4x+1073=17x+1010 | | 12+x–8=7x+5–5x | | 6x-2(2+8x)=10+4 | | 5y-9=6y-4 | | (1/2)k=3.2 | | 1.03^x=36 | | 4/3g+1/6=7/6 | | -5a+36=16 | | x+1/6= |

Equations solver categories